Comparison of Alendronate and Pamidronate on Bone Loss in Kidney Transplant Patients for the First 6 Months of Transplantation (Iranian Journal of Kidney Diseases, 2011)
Introduction. Osteoporosis develops and progresses in a considerable number of kidney transplant patients. Bisphosphonates, which are used for prevention and treatment of osteoporosis, may accentuate gasterointestinal complications and lead to more nonadherence to treatment. This randomized clinical trial was conducted to compare the effect of pamidronate versus alendronate  on early bone mineral density changes in kidney transplant patients. Materials and Methods. Forty  patients (27 men and 13 women), aged from 20 to 58 years, with low bone mineral density (T score < -2) in the spine, total hip, or femur neck were enrolled. Participants were randomly allocated into 2 groups to receive pamidronate or alendronate. The pamidronate group received intravenous pamidronate, 90 mg, starting from the 3rd week of transplantation for 3 months. The alendronate group started to receive oral alendronate, 70 mg per week for the same period. At baseline and 6 months, bone mineral density was measured by dual-energy x-ray absorptiometry. Gastrointestinal side effects were monitored every month. Results. No significant difference was found in bone density changes of the lumber area between the two groups; however, significantly less reduction in bone mineral density of the femur neck and femur occurred in the pamidronate group. Kidney function and parathyroid hormone levels were similar in the two groups before and after the study. Gastrointestinal side effects were seen in 3 patients of the alendronate group only. Conclusions. Pamidronate was comparable to alendronate in prevention of early bone loss after kidney transplantation.